PENGARUH INFLUENCER MARKETING, BRAND AWARENESS DAN KOMUNIKASI PEMASARAN (VIRAL MARKETING) DI SOSIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN - Nadea Apriliani; Sri Ekowati (UM. Bengkulu, 2023)
This study aims to determine the effect of influencer marketing, brand awarreness, and marketing communication (viral marketing) in social media on purchasing decisions for implora products at Bengkulu Muhammadiyah University students, both partially and simultaneously. There are several factors that will be discussed in this study, including influencer marketing, brand awareness, and marketing communication (viral marketing). The object of this research is management students at Muhammadiyah University of Bengkulu, totaling 175 people. In this study the authors used data collection methods by means of observation, interviews and distributing questionnaires. Data analysis techniques in this study, using instrument tests, classical assumption tests, respondent response analysis, multiple linear regression analysis, hypothesis testing and coefficient of determination analysis. The results showed that influencer marketing has a positive and significant effect on purchasing decisions, then brand awareness has a positive and significant effect on purchasing decisions and marketing communication (viral marketing) has a positive and significant effect on purchasing decisions. So, from the results of the research that has been done, it can be concluded that influencer marketing, brand awareness and marketing communication (viral marketing) have a partial and simultaneous effect on purchasing decisions for implora products for students of the muhammadiyah university of Bengkulu. Â Keywords: Influencer Marketing, Brand Awareness, Marketing Communication (Viral Marketing) and Purchasing Decisions.